FEMINISME DALAMNOVELBIDADARI TERAKHIR KARYAAGNES DAVONAR - Eva Ida Nuraini (PENTAS : Pendidikan Bahasa dan Sastra Indonesia, 2018)
This research was leading to the struggle of life main character in the novel that is Eva in the novel of Bidadari Terakhir byAgnes Davonar. This novel inspired women to be a strong woman and full of sacrifice in accepting one's fate inherlife. Author elaboratedwell be difficult life they experienced. Therefore, the purpose of this research was to describe (1) the character of Eva and (2) the struggle of feminism figure in the novel of Bidadari Terakhir by Agnes Davonar. The method used in this studywasa descriptive qualitative. This research resulted in two things: (1) concerning the character of Eva, of the characters that appear in each quote gives a great overview over the difficulties of life to affect her character, women are tough and full of sacrifice, (2) of the struggle of character Eva in the novel of Bidadari Terakhir by Agnes Davonar, Eva efforts in alleviating the economic burden of the family is to decide to work as a prostitute even though her family did not know her work, starting from the encounter with Rasya, Eva got a job that is more humane.